Abuse Of Authority By State Officials In Corruption Cases: The Case Of Complete Systematic Land Registration Program - Hadi Prayitno, Ahmad; Wahyono, Dwi; Bagaskoro, M Rizal (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
The judge’s decision in the corruption case involving the abuse of authority in The Complete Systematic Land Registration (Pendaftaran Tanah Sistematis Lengkap or PTSL) program underscores the importance of legal certainty in holding perpetrators accountable for actions that harm state and community finances. This research aims to examine and analyze the abuse of authority by state administrators in corruption cases, the accountability of the perpetrators in PTSL-related corruption, and the prevention of corruption in the implementation of complete systematic land registration. The research employs a normative juridical approach. The findings indicate that the accountability of the perpetrators clearly meets the elements outlined in Article 3 in conjunction with Article 18 of the Corruption Law. Abuse of authority, as an element of corruption in Indonesia, manifests in actions that contradict the public interest or benefit individuals, groups, or other parties, as well as the misuse of procedures intended to achieve specific goals. The ideal concept for combating corruption, as adopted by the government and applied to future PTSL implementation, is the establishment of a non-criminal, institution-based prevention and education unit focused on addressing corruption.